2016
DOI: 10.1136/jclinpath-2015-203265
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Claudin 12 in estrogen receptor-negative breast cancer

Abstract: The findings suggest that CLDN 12 expression could be clinically useful for predicting the survival of the ER-negative subgroup of patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The evaluation of claudins expression was also suggested to increase the possibility of creating new drugs. Iravani and co-workers showed that expression of claudin-12 is upregulated in estrogen receptor (ER)-negative breast cancer and its expression is associated with poor prognosis, indicating that claudin-12 may serve as a marker for predicting the survival in this cancer subtype [79]. The overexpression of claudin-6 was showed to inhibit migration and invasion of MCF-7 cells [104].…”
Section: Claudins In Breast Cancermentioning
confidence: 99%
“…The evaluation of claudins expression was also suggested to increase the possibility of creating new drugs. Iravani and co-workers showed that expression of claudin-12 is upregulated in estrogen receptor (ER)-negative breast cancer and its expression is associated with poor prognosis, indicating that claudin-12 may serve as a marker for predicting the survival in this cancer subtype [79]. The overexpression of claudin-6 was showed to inhibit migration and invasion of MCF-7 cells [104].…”
Section: Claudins In Breast Cancermentioning
confidence: 99%
“…The non-canonical claudins-12 and -25 were also expressed at levels above background in both pregnancy and lactation with significant increases during lactation. There is a little data on mammary claudin-12; it showed weak cytoplasmic staining in normal breast cells adjacent to breast tumors, but was upregulated in some tumors [59]. Its expression increased MCF-7 cell migration [60], but nothing is currently known about its function in the normal mammary epithelium.…”
Section: Part 2: Claudin Expression and Localization During Mammary Gmentioning
confidence: 99%
“…Claudins are known to act as barriers for the diffusion of solutes between epithelial cells, participating in the regulation of water transportation, ions and certain macromolecules. Therefore, it is a reasonable hypothesis that claudins are likely to be involved in carcinogenesis (18). …”
Section: Introductionmentioning
confidence: 99%
“…However, the claudin superfamily of integral membrane proteins is composed of numerous isotypes (15,16,18), and there is some heterogeneity in study results when claudin subtypes are evaluated. Claudin 1 has been identified as a novel survival factor in basal-like breast cancers, as downregulation of claudin 1 was shown to induce cell death in breast cancer cell lines (17).…”
Section: Introductionmentioning
confidence: 99%